Patient-Reported Outcome Measures and Clinical Outcomes in Children with Foregut Anomalies - Isabel I. Sreeram; Chantal A. ten Kate; Joost van Rosmalen; Johannes M. Schnater; Saskia J. Gischler; René M. H. Wijnen; Hanneke IJsselstijn; André B. Rietman (MDPI AG, 2021)
Increasing numbers of children and adults with chronic disease status highlight the need for a value-based healthcare system. Patient-reported outcome measures (PROMs) are essential to value-based healthcare, yet it remains unclear how they relate to clinical outcomes such as health and daily functioning. We aimed to assess the added value of self-reported PROMs for health status (HS) and quality of life (QoL) in the long-term follow-up of children with foregut anomalies. We evaluated data of PROMs for HS and/or QoL among eight-year-olds born with congenital diaphragmatic hernia (CDH), esophageal atresia (EA), or congenital lung malformations (CLM), collected within the infrastructure of a multidisciplinary, longitudinal follow-up program. Clinical outcomes were categorized into different outcome domains, and their relationships with self-reported HS and QoL were assessed through multivariable linear regression analyses. A total of 220 children completed HS and/or QoL self-reports. In children with CDH and EA, lower cognition was significantly associated with lower self-reported HS. Due to the low number of cases, multivariable linear regression analysis was not possible in children with CLM. HS, QoL, and clinical outcomes represent different aspects of a child's wellbeing and should be measured simultaneously to facilitate a more holistic approach to clinical decision making.